The effect of intense special exercises to rehabilitate second-degree external collateral ligament tear in young handball players - Mahmood, Hasnaa; Ismaeil, Karam (Journal of Physical Education, 2023)
The research problem is crystallized by the spread of injury to the external collateral ligament of the knee joint among young handball players, in addition to the reluctance of most players from rehabilitation programs. The research aims to prepare special intensive exercises to rehabilitate second-degree external collateral ligament tears in young handball players and to identify their effect. It is assumed that the research found that there were statistically significant differences in all variables of the study. As for the research sample, they were chosen intentionally and numbered (6) young handball players with torn external collateral ligaments for the period between (8/2/2023) and (15/10/2023) and they are homogeneous in the degree of injury, second-degree tear. The researchers used the statistical package (SPSS) to process the data statistically. According to the results collected, it was concluded that the intense special exercises had a positive and effective effect in the return of injured young players to the playing field, as it contributed to the return of strength. The muscles surrounding the joint and its range of motion are as close as possible to the normal state. They recommended using these exercises as guidance for rehabilitating those injured in other sports.